Microbial Bioremediation: A Potential Tool for Restoration of Contaminated Areas - Das, S.; Dash, H.R.
Due to rapid industrialization and large-scale anthropogenic activities, the pollution level is increasing at a rapid rate, which is a major concern. Though many remediation techniques are available, the use of microorganisms has many advantages like cost effectiveness, few or no by-products, reusability, and more. Microorganisms are readily available, rapidly characterized, highly diverse, omnipresent, and can use many noxious elements as their nutrient source. They can be applied in both in situ and ex situ conditions; in addition, many extreme environmental conditions can be cleaned by such entities. Most countries do not restrict industrialization in spite of increased pollution levels; however, these can be minimized using suitable remedial measures, particularly where microorganisms provide a useful tool for a better alternative. In this chapter, the role of microbes in bioremediation, their superiority over other mechanisms, and the implications of such tiny organisms for cleaning the environment will be discussed. © 2014 Elsevier Inc. All rights reserved.
Keywords: BACTERIA; BIOREMEDIATION; EXTREME ENVIRONMENT; GENETIC MANIPULATION